2006
DOI: 10.1097/00004703-200612000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Pediatric Patients with Irritable Bowel Syndrome:

Abstract: The primary aim of the study was to investigate the generic health-related quality of life (HRQOL) of pediatric patients meeting Rome II criteria for irritable bowel syndrome (IBS) in comparison to healthy children. The secondary aim was to compare pediatric patients with IBS to pediatric patients with Rome II criteria diagnosed functional abdominal pain (FAP) and patients with diagnosed organic gastrointestinal (GI) disorders. The study also investigated the associations between GI symptoms with generic HRQOL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
119
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(136 citation statements)
references
References 27 publications
17
119
0
Order By: Relevance
“…Results for the sample on the PedsQL are similar to those recently reported for a smaller (n = 42) population of children and adolescents with inflammatory bowel disease (33) and higher than reported for adolescents with a variety of gastrointestinal disorders (23). These results help to confirm the validity of the IBD-specific measure.…”
Section: Discussionsupporting
confidence: 85%
“…Results for the sample on the PedsQL are similar to those recently reported for a smaller (n = 42) population of children and adolescents with inflammatory bowel disease (33) and higher than reported for adolescents with a variety of gastrointestinal disorders (23). These results help to confirm the validity of the IBD-specific measure.…”
Section: Discussionsupporting
confidence: 85%
“…19,26,28 IBS is more prevalent among girls than among boys and is associated with high risk of mental health problems and of co-morbid pain at other body sites. 25,26,51 There is broad agreement that IBS is best conceptualized in terms of the biopsychosocial model, with multiple factors contributing to its pathophysiology. 6,9,16,21,29,34,49 These factors are incompletely understood, but are likely to include both peripheral gut factors, 5,27 as well as central factors, including central pain modulation, 40 and disorders of mood and affect.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have confirmed children with pain predominant FGIDs are having poor health related quality of life. 17,18 We have recently shown that children with FC have poor health-related quality of life (HRQoL) and suffer from number of somatic symptoms which contribute to spiral down their HRQoL further. 19 Sagawa et al 20 noted children with IBS have poor school performances indicating long term repercussions of FGDs in children.…”
Section: Commentmentioning
confidence: 99%